2021
DOI: 10.1016/j.jctube.2021.100277
|View full text |Cite
|
Sign up to set email alerts
|

One year of COVID-19 and its impact on private provider engagement for TB: A rapid assessment of intermediary NGOs in seven high TB burden countries

Abstract: The COVID-19 pandemic has impacted health systems and health programs across the world. For tuberculosis (TB), it is predicted to set back progress by at least twelve years. Public private mix (PPM) is a collaborative approach to engage private providers in quality TB care. It has made a vital contribution to reach End TB targets with a ten-fold rise in TB notifications from private providers between 2012 and 2019. This is due in large part to the efforts of intermediary agencies, which aggregate demand from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“… 23 Moreover, concern about contracting the virus when visiting health-care facilities also could affect the whole agenda of early diagnosis and seeking care. 24 These facilities have minimized their services to reduce the risk of transmission. Most TB hospitals in Indonesia have been designated COVID-19 hospitals at provincial levels, leading to a significant delay in TB diagnosis because of additional workload.…”
Section: Challenges In Controlling Tb During the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 Moreover, concern about contracting the virus when visiting health-care facilities also could affect the whole agenda of early diagnosis and seeking care. 24 These facilities have minimized their services to reduce the risk of transmission. Most TB hospitals in Indonesia have been designated COVID-19 hospitals at provincial levels, leading to a significant delay in TB diagnosis because of additional workload.…”
Section: Challenges In Controlling Tb During the Pandemicmentioning
confidence: 99%
“…Nevertheless, their contribution to support TB services drastically increased since the end of 2020. 24 These activities could not be implemented because of several factors, such as travel restrictions. This situation might hinder ending TB by 2035, as the UN and WHO targeted.…”
Section: Challenges In Controlling Tb During the Pandemicmentioning
confidence: 99%
“…Other detailed reports of facility closures, service disruptions, and increases in costs for patients have begun to be published [15,16,31,32]. The results of our study agree with results obtained in a previous rapid assessment by Klinton et al on the impact of the pandemic on TB services in the private sector in seven high-burden TB countries including Nigeria [16]. This rapid assessment reported fear of COVID-19 infection in facilities on both the patient and provider side, which was heightened by the overlapping TB and COVID-19 symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…After five weeks of a federally mandated lockdown, restrictions were gradually eased. COVID-19 infection control measures were implemented early in the pandemic to reduce infection and disease transmission; however, earlier reports indicated that they also led to challenges in accessing health services, especially for already vulnerable populations such as individuals with TB in Nigeria [6,14,15], as they did in other high burden countries [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a recent report estimated that Indonesian healthcare workers had a five times higher chance of death from COVID-19 than the general population. 33,34 Second, the pandemic affected patient health-seeking behaviour as well as access to essential health services, because of fear of contracting COVID-19 and extra costs for personal protective equipment 35 , and government-mandated local lockdowns. 36 Third, emerging data suggest that biological interactions between both pathogens can result in shared dysregulation of immune responses and a dual risk for COVID-19 severity and TB disease progression or poor outcomes.…”
Section: Discussionmentioning
confidence: 99%